Scale of differentiated service delivery implementation in HIV care facilities in low‐ and middle‐income countries: a global facility survey - Nathalie Verónica Fernández Villalobos; Fabrice Helfenstein; Vohith Khol; Christella Twizere; Mayara Secco; Barbara Castelnuovo; Jacqueline Huwa; Thierry Tiendredbeogo; C. William Wester; Siew Moy Fong; Gad Murenzi; Yanink Caro‐Vega; et al. (Journal of the International AIDS Society)
Abstract Introduction In 2016, the World Health Organization recommended differentiated service delivery (DSD) as a client‐centred approach to simplify HIV care in frequency and intensity, thus reducing the clinic visit burden on individuals and HIV programmes. We describe the scale of DSD implementation among HIV facilities in low‐ and middle‐income countries (LMICs) in Latin America, Africa and the Asia‐Pacific before the COVID‐19 pandemic. Methods We analysed facility‐level survey data from HIV care facilities participating in the International epidemiology Databases to Evaluate AIDS consortium in 2019. We used descriptive statistics to summarise the availability of DSD, multi‐month dispensing (MMD) and DSD for HIV treatment models. We explored factors associated with DSD implementation using multivariable models. Results We included 175 facilities in the Asia‐Pacific (n = 30), Latin America (n = 8), Central Africa (n = 21), East Africa (n = 74), Southern Africa (n = 28) and West Africa (n = 14). Overall, 133 facilities (76%) reported implementing DSD. Of these, 91% offered DSD for HIV treatment, 61% for HIV testing and 59% for antiretroviral therapy (ART) initiation. The most common duration of ART refills for clinically stable clients was 3MMD, (70%), followed by monthly (14%) and 6MMD (10%). Facility‐based individual models were the most frequently available DSD for the HIV treatment model (82%), followed by client‐managed group models (60%). Out‐of‐facility individual models were available at 48% of facilities. Facility‐based individual models were particularly common among facilities in East (92%) and Southern Africa (96%). Facilities in medium and high HIV prevalence countries, and those with 3MMD, were more likely to implement DSD. Conclusions In 2019, DSD was available in most HIV care facilities globally but was not evenly implemented across regions and HIV services. Most offered facility‐based DSD for HIV treatment models and 3MMD for clinically stable clients. Efforts to expand DSD for HIV testing and ART initiation and to offer longer MMD can improve long‐term retention in care of people living with HIV in LMICs, while further alleviating the operational burden on healthcare services. These findings from the pre‐COVID‐19 era underline the need for strengthening DSD in HIV care, which remains at the centre of current efforts towards client‐centred care.